Determination of Atmospheric Particulate Matter and Heavy Metals in Air of Tabriz City, Iran - Sanobari, Fariba; Banisaeid, Sepideh (Asian Journal of Chemistry, 2012)
A network of seven sampling stations for the monitoring of elemental concentration of SPM in the air of Tabriz was established. Sampling was carried out from October 2002 and continued until September 2003. Instrumental neutron activation analysis (INAA) and atomic absorption spectrometry (AAS) methods were employed to obtain the monthly concentrations of V, Ca, Al, Fe, Mn, Sc and Zn in Tabriz air. The mean annual concentration (in μg/m3) of 8 elements were found to be : Ca 12.065 (± 17.33 %), Al 2.207 (± 49.94 %), V 0.007 (± 21.47 %), Fe 1.829 (± 57.21 %), Sc 0.0007 (± 25.84 %), Mn 0.038 (± 36.07 %) and Zn 0.102 (± 25.17 %), Pb concentration has already been studied. The results of the study show that vehicle (traffic) pollution in Tabriz air is higher than WHO and EPA standards and natural and industrial pollution are exceeding international guidelines in some seasons.